Effect Of Air Gap Distance On The Structure, Characteristic And Performance Of PES/PVP And PES/PVP/ZnO Hollow Fiber Membrane - Razak, Muhammad Hanafi (Universiti Sains Malaysia, 2018)
Polyethersulfone (PES) membrane commonly used in the application of water treatment for humic acid removal. Fouling of membrane is one of unfavourable effect during membrane separation process. To overcome this fouling effect on membrane, some research as stated improving hydrophilicity of the membranes can lead in reducing this unfavourable effect. An addition of ZnO-NPs in PES membrane and varying the air gap length during fabrication process of hollow fibre membrane is techniques to improve the hydrophilicity of the membrane. This PES hollow fiber with addition of ZnO-NPs undergoes systematic study of the air gap length effect on the membrane’s morphology and the separation performance. The dope solution consist of PES, ZnO and Polyvinylpyrrolidone (PVP) is used for fabrication of the hollow fibre membrane using dry-jet wet spinning process. At a same time the air gap length parameter are varies (5cm, 10 cm, 15cm) to provide further hydrophilicity enhancement. The morphology of the hollow fibre membrane is analysed by using atomic force microscopy (AFM) and scanning electron microscopy (SEM) for evaluation of inner and outer surface of membranes and their cross-sectional structure respectively. An addition of ZnO nanoparticle into PES membranes is proven to improve the hydrophilicity and lead to reduce fouling effect of the membrane due to well disperse of ZnO-NPs through membrane. For hollow fibre membrane evaluation, 50 mg/L of humic acid solution at pH 7.7 is used as feed and it result at highest flux obtained at higher air gap meanwhile higher HA rejection at low air gap length. The flux recovery ratio (FRR) can increase up to 99.522 % and the recovery flux ratio (RFR) can reduced to 7.182% for the highest air gap length. Besides, the Z1-15 membrane with 15 cm air gap length shows the highest HA permeate flux of 124.675 kg/m2.h under 1 bar transmembrane pressure and it show the lowest antifouling compared to other membrane. Nevertheless, the highest humic acid rejection was found at Z1-5 membrane which at 5cm air gap length with 96.6%.